An evaluation of pre-service teachers’ practical experience in teaching mathematics - Mark Mishiwo (Journal Focus Action of Research Mathematic (Factor M), 2025)
The research evaluated the field practices of pre-service teachers teaching mathematics under mentor supervision during Ghana’s Supported Teaching in Schools programme. Recognizing the critical role of mentoring in shaping effective and reflective teaching practices, the research aimed to assess the extent of mentor support in four key areas: developing critical perspectives, guiding lesson planning, modeling instructional practices, and providing feedback. A descriptive quantitative design was employed, with the use of an organized questionnaire constructed using a Likert scale with five points. The lottery approach randomly selected pre-service teachers. The sample comprised 83 Level 400 Bachelor of Education Mathematics students from Akatsi College of Education. Descriptive statistics were used to analyze the collected data, including means, standard deviations, and skewness. Findings revealed that mentor modeling of teaching and provision of feedback were the most supported areas, with mean scores of 3.37 and 3.13, respectively. Support for developing critical perspectives was moderate (M = 3.14), while guidance in lesson planning was notably low (M = 2.59). Low standard deviations and negative skewness indicated relatively consistent and positively skewed responses across participants. The findings suggest that although mentor support exists, it is often inconsistent and lacks depth, particularly in collaborative planning and reflective engagement. This study contributes to the discourse on improving mentor training and underscores the need for structured, reflective, and sustained support in pre-service mathematics education. An upcoming research could examine the long-term effects of mentoring and explore how digital pedagogies can be integrated into mathematics instruction.